Private sector vaccine share in overall immunization coverage in India: Evidence from private sector vaccine utilization data (2012-2015) - Habib Hasan Farooqui; Sanjay Zodpey (Wolters Kluwer Medknow Publications, 2020)
The objective of this research was to generate the evidence on the private sector's contribution to overall immunization coverage for selected pediatric vaccines in India. Using IMS Health's (now IQVIA) vaccine sales audit data and innovative methodological approach we estimated private-sector vaccine share in the total immunization coverage across selected pediatric vaccines in India. Our estimates suggest that private sector remains an important contributor to immunization services in India not only for Universal Immunization Program vaccines (Bacillus Calmette-Guérin [19.23%], HiB pentavalent [11.09%], hepatitis B [5.75%], oral poliovirus vaccine [5.48%], Diphtheria-Pertussis-Tetanus [2.66%], and measles [2.17%]) but also for newer vaccines (hepatitis A [4.2%], rotavirus [3.4%], typhoid [3.3%], and pneumococcal conjugate vaccine [2.5%]). As the private sector continues to remain an important access point for immunization services in the country, avenues for potential synergy between public and private sectors should be explored to improve the coverage and quality of immunization services.